Validation of HDR brachytherapy doses in the treatment of keloid scars using the egs_brachy Monte Carlo application - Saikkonen Aleksi; Ojala Jarkko; Sipilä Petri; Boman Eeva; Keyriläinen Jani (IOP Publishing Ltd, 2025)
Objective
Radiotherapy is a well-known alternative in the treatment of keloid scars to reduce the recurrence of scars. The purpose of this study was to investigate the feasibility and accuracy of dose delivered from a high-dose-rate (HDR) afterloaders in keloid scar brachytherapy using Monte Carlo (MC) simulations and measurements.
Approach
Treatment doses and central axis dose profiles were measured using radiophotoluminescence dosimeters and radiochromic films, respectively, with two HDR afterloaders, both using an Ir-192 source, in a phantom made of solid water and polycarbonate sheets. The nominal treatment dose calculated by the AAPM Task Group No. 43 (TG-43) dose model was set to 8.5 Gy at a distance of 0.5 cm laterally from the middle of the source line located in a plastic applicator simulating a 15 cm long surgically removed scar treatment with 30 equally spaced (0.5 cm) source positions. The dose profiles were measured at three different distances from the applicator and the absolute doses at four points at different distances. MC simulations were performed using the egs_brachy, which is based on EGSnrc code system.
Main results
The measured and simulated dose profiles match well, especially at 10.0 mm (difference <1%) and 15.0 mm depths (difference <4%), and with a small dose difference at 5.0 mm depth (difference <4%). Point dose measurements agreed well in the dose maximum area (difference <7%) with the simulated dose profiles, although the largest difference near the edge of the profile was <30%. The dose differences between the TG-43 dose model and the MC simulation were small (differences <4%).
Significance
Simulated and measured dose levels at a depth of 0.5 cm showed that the nominal treatment dose can be achieved with the utilized setup. The measurement results of the absolute dose agree well with the corresponding simulation results.